Paradigma Islam Wasatiyah Ulama Aceh: Studi Pemikiran Tu Sop Jeunib - Teuku Zulkhairi (DAYAH: Journal of Islamic Education, 2022)
This article describes the Islamic thought of Wasaṭiyah one of the Acehnese scholars, Tgk. H. Muhammad Yusuf A. Wahab or well-known as Tu Sop Jeunieb and currently serves as Chairman of the Ulama Dayah Aceh Association (HUDA). Tu Sop is active in preaching by word and deed. To expand the reach of his da'wah, Tu Sop also utilizes modern da'wah facilities such as social media, radio, websites, and others. The scope of his da'wah includes political, social, moral, and spiritual aspects, aqidah, motivation and education. This research uses a qualitative approach and focuses on the thoughts of the characters. Data were collected through document review, observation, and in-depth interviews. The data were then analyzed interpretively. The results of the study show that Tu Sop Jeunieb's thoughts emphasize aspects of the Islamic moderation approach or the "middle" view in religion. Tu Sop's narrative is always in the middle between two clashes with the aim of finding common ground in differences. Tu Sop looked at the Ahlusunnah wal Jamā’ah in a Wasaṭiyah manner. He also consistently to invite unity (Wiḥdat al-Ummah), have character and maintain a sense of security, balance between the world and the hereafter, balance between reason and sacred texts, orientation to goodness, hikmah and good advice, reject all kind of deviation. The results of this study are very important as a guide in grounding the concept of Wasaṭiyah Islam which is increasingly needed lately, especially when Muslims are faced with various potential conflicts and divisions.